Settler Colonialism and Labour Studies in Canada: A Preliminary Exploration - Camfield, David (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
The 21st century has seen growing attention to settler colonialism among academic researchers in Canada and internationally. In the Canadian context, interest has been fuelled above all by an ongoing resurgence of Indigenous activism and intellectual work, of which the most visible expression to most non-Indigenous people was the Idle No More movement of 2012–13. To date, however, little attention has been paid to settler colonialism within labour studies, broadly understood. As a modest contribution to remedying this deficiency, this article argues for the importance of understanding Canada as a settler-colonial society, proposes a conceptualization of settler colonialism from the perspective of a historical materialism reconstructed through engagement with Indigenous anticolonial thought, and offers some preliminary reflections on integrating analysis of settler colonialism into historical and contemporary research on labour.